Determinan Minat Beli Konsumen pada Adidas Sportwear - Dessy Dwiyanti (Journal Of Business, Finance, and Economics (JBFE), 2024)
The sports product business is an important pillar in the progress of national sports. This can be seen from the high popularity of sales of sports products in society, both from sellers and buyers who both want to make a profit. Understanding the factors that influence consumer buying interest is the key for business people to gain profits and increase market share in this industry. This research is a type of quantitative research and uses a purposive sampling technique of one hundred respondents. The analysis method in this research uses quantitative primary data, the test stages carried out are: validity test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2). The research results show that advertising influences consumer buying interest, endorsement services influence consumer buying interest, the marketing system influences consumer buying interest and the payment system influences consumer buying interest. The Fcount results show that Ho is rejected and Ha is accepted, so it can be concluded that the variables of advertising, endorsement services, marketing systems and payment systems simultaneously influence consumer buying interest.